Organizational agility in public and private schools - Eghbal, Farzaneh; Hoveida, Reza (International Journal of Education and Cognitive Sciences, 2022)
Introduction: Agility means the ability to respond to rapid and successful response to environmental changes and is an important factor for the effectiveness of schools. Agile school represents the response when exposed to internal and external changes.  So, the present study aims to investigate and compare the organizational agility in public and private schools of Isfahan. Materials and method: Employing stratified random sampling, 286 persons were selected by stratified random sampling. Researcher made questionnaire based on Sharif and Zhang's model (2000) were used to assess Organizational agility.Results: finding presented significant differences between the mean score of agility at public and private schools. Additionally in regard of sub variables there was a significant difference between accountability and competence, but in the case of speed and flexibility no significant difference in average were found.Conclusion: for achieving Better Organizational agility, quality of educational and fundamental services should be increased and the reduction of costs, internal satisfaction of the students should be considered in the face of rapid changes in education system and training time associated with changes in the education system